Omni-Directional Impact Micro switch with Extended Holding Time - Shuangjie Liu; Yongping Hao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The Omni-directional impact MEMS switch was designed and characterized for the purpose of impact sensing. In order to turn on the circle reliably, the connect time should be long enough, the structure of flexible electrode was designed to extend the holding time. The structure consists of electrode A and B, electrode A is the sensing mass simultaneously, the sensing mass is suspended by helix cantilever that is fixed to the pedestal, the outer ring is the electrode B, which is suspended by helix cantilever that is fixed to the outer frame. Between the two electrodes, there is a gap, the gap separates electrode A and B, thereby keeping the switch in the open state. The distortion during the impact process extended the contact time. The dynamics of the switch is simulated, the simulation results show that the response time of the switch is 0.135ms, it is short enough, and the contact time which is also called holding time is about 20, the extended time make the switch turn on more reliably. These results satisfy the required specifications for the ammunition systems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2473